On the Method Appropriate to Hayek Studies - Scott Scheall (Œconomia, 2019)
The paper considers the significance of F. A. Hayek’s writings on the study of complex phenomena for the study of the very complex phenomena of Hayek’s own life and career. It is argued that the methodological principle which Hayek recommended for the investigation of complex phenomena is applicable to explanations of his own intellectual development. Indeed, it is argued that the extent to which a Hayek scholar respects this principle in their attempts to explain Hayek’s life and career is the first criterion by which such attempts should be evaluated. As Hayek himself might have put it, an explanation of some part of his career that neglects its inherent complexity is “probably merely of necessity false” (Hayek, [1964] 2014, 263).